A Systematic Review of Assessments and Interventions for Chronic Pain in Young Children With or at High Risk for Cerebral Palsy. (August 2021) - Letzkus, Lisa; Fehlings, Darcy; Ayala, Lauren; Byrne, Rachel; Gehred, Alison; Maitre, Nathalie L.; Noritz, Garey; Rosenberg, Nathan S.; Tanner, Kelly; Vargus-Adams, Jilda; Winter, Sarah; Lewandowski, Dennis J.; et al.
Background: Pain is common in children with cerebral palsy. The purpose of this systematic review was to evaluate the evidence regarding assessments and interventions for chronic pain in children aged ≤2 years with or at high risk for cerebral palsy. Methods: A comprehensive literature search was performed. Included articles were screened using PRISMA guidelines and quality of evidence was reviewed using best-evidence tools by independent reviewers. Using social media channels, an online survey was conducted to elicit parent preferences. Results: Six articles met criteria. Parent perception was an assessment option. Three pharmacologic interventions (gabapentin, medical cannabis, botulinum toxin type A) and 1 nonpharmacologic intervention were identified. Parent survey report parent-comfort and other nonpharmacologic interventions ranked as most preferable. Conclusion: A conditional GRADE recommendation was in favor of parent report for pain assessment. Clinical trials are sorely needed because of the lack of evidence for safety and efficacy of pharmacologic interventions.